2019
DOI: 10.1116/1.5057741
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects on the performance of epoxide-based negative-tone molecular resists

Abstract: Several 0.26N tetramethylammonium hydroxide (TMAH)-soluble epoxide molecular resists have been synthesized and are reported here. Previously, the patterning performance of 1,1,2,2-tetrakis(p-hydroxyphenyl)ethane-3 epoxide (TPOE-3Ep) was reported and resolved 26 nm lines using extreme ultraviolet lithography. Here, a deeper study is performed to determine the effects of various structural features on the lithographic performance of 0.26N TMAH-soluble molecular resists. Increasing the number of phenols resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Different photoresists are matched with different baking process parameters, and sometimes different baking parameters can be applied to the same polymer-based photoresist. It is reported that the glass transition temperatures of some epoxide-based negative-tone molecular glass photoresists are generally lower than 100°C [ 36 38 ], while the glass transition temperature of BPA-6OH negative photoresist is much higher. This high glass transition temperature can meet the requirement of the lithographic processes.…”
Section: Resultsmentioning
confidence: 99%
“…Different photoresists are matched with different baking process parameters, and sometimes different baking parameters can be applied to the same polymer-based photoresist. It is reported that the glass transition temperatures of some epoxide-based negative-tone molecular glass photoresists are generally lower than 100°C [ 36 38 ], while the glass transition temperature of BPA-6OH negative photoresist is much higher. This high glass transition temperature can meet the requirement of the lithographic processes.…”
Section: Resultsmentioning
confidence: 99%